Evaluating the impact of sprouting conditions on the glucosinolate content of Brassica oleracea sprouts - Vale, Ana Paula (2022)
The glucosinolates content of brassica plants is a distinctive characteristic, representing a healthy advan- tage as many of these compounds are associated to antioxidant and anti-carcinogenic properties. Brassica sprouts are still an underutilized source of these bioactive compounds. In this work, four varieties of bras- sica sprouts (red cabbage, broccoli, Galega kale and Penca cabbage), including two local varieties from the North of Portugal, were grown to evaluate the glucosinolate profile and myrosinase activity during the sprouting. Also the influence of light/darkness exposure during sprouting on the glucosinolate content was assessed. Glucosinolate content and myrosinase activity of the sprouts was evaluated by HPLC meth- ods. All sprouts revealed a higher content of aliphatic glucosinolates than of indole glucosinolates, con- trary to the profile described for most of brassica mature plants. Galega kale sprouts had the highest glucosinolate content, mainly sinigrin and glucoiberin, which are recognized for their beneficial health effects. Penca cabbage sprouts were particularly richer in glucoraphanin, who was also one of the major compounds in broccoli sprouts. Red cabbage showed a higher content of progoitrin. Regarding myrosi- nase activity, Galega kale sprouts showed the highest values, revealing that the use of light/dark cycles and a sprouting phase of 7?9 days could be beneficial to preserve the glucosinolate content of this variety.